PENGELOLAAN SEKOLAH DASAR BERBASIS PENDIDIKAN KARAKTER MELALUI PERAN SERTA MASYARAKAT DI DKI JAKARTA - Arita Marini (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2019)
The aim of this study is to know the effectiveness of school management based on character education through community involvement at elementary schools in the Province of DKI Jakarta. This research used survey method for 145 principals done at 145 elementary schools in Jakarta. The questionnaires of school management based on character education through community involvement at elementary schools in the Province of DKI Jakarta are related to inviting society to school to give spiritual knowledge, involving society to participate in school security, involving society to participate in deciding school programs containing character values, involving society to solve the school problems related to character education, involving society to get involved in school committees, involving society to give facilities related to character education to school, involving society to help to control the implementation of character education at school, cooperating with health workers to give health service to students, conducting routine meeting between school and societies to solve the problems related to character education, cooperating with society to keep environmental cleanliness at school, involving society to assist traffic security and order surrounding school, involving society to sacrifice animals on Idul Adha Day, involving society in extracurricular activities to find the trainers, involving society to find the cleanliness workers, involving society to participate in creating healthy canteen at school, involving society to participate in controlling the activities at school, involving society to participate in preventing dengue fever outbreak, cooperating with private institution in giving cleanliness service at school, and cooperating with society to conduct art performance at school. The result of study showed that the effectiveness of school management based on character education through community involvement higher than average scores reached 24.80 % and less than average scores reached 64.90 %. Effectiveness of school management based on character education through community involvement at 145 elementary schools in the Province of DKI Jakarta reached 75.53 %. It can be concluded that the effectiveness of school management based on character education through community involvement at 145 elementary schools in the Province of DKI Jakarta hasn’t been optimal so that some improvement and adjustment have to be done.